Lifetime disadvantage, discrimination, and the gendered workforce - Bisom-Rapp, Susan
"Lifetime Disadvantage, Discrimination and the Gendered Workforce fills a gap in the literature on discrimination and disadvantage suffered by women at work by focusing on the inadequacies of the current law and the need for a new holistic approach. Each stage of the working life cycle for women is examined with a critical consideration of how the law attempts to address the problems that inhibit women's labour force participation. By using their model of lifetime disadvantage, the authors show how the law adopts an incremental and disjointed approach to resolving the challenges, and argue that a more holistic orientation towards eliminating women's discrimination and disadvantage is required before true gender equality can be achieved. Using the concept of resilience from vulnerability theory, the authors advocate a reconfigured workplace that acknowledges yet transcends gender"--